Sociography: Writing Differently. Issue 4 (July 2022) - Kilby, Jane; Gilloch, Graeme
Sociology is just as much an art form as it is a science. And while sociologists and those in cognate disciplines have long experimented with their writing, the search for new academic forms and practices has acquired new urgency and potentiality. How we write up our research is of paramount importance: our language can be used in experimental and innovative ways to offer nuanced, critical commentary without foreclosing alternative viewpoints, and without excluding others from dialogue. Sociography offers spaces for new sensibilities and sensitivities; unresolved or incomplete argument; multiple, multi-dimensional and multiplying possibilities: for writing differently. As an intervention in writing the social, our collection works to resist the ideological promotion of dry, dispassionate, and seemingly 'objective' discourse, one which has traditionally upheld a set of dominant, privileged voices. And in so doing, our collection explores the potential of new ways of writing the social for both a trans- and post-disciplinary academy and a wider reading public; and seeks forms of writing that do justice to the critical curiosity that animates sociology. In sum, the challenge embraced by this collection is to argue for and showcase a praxis that activates sociological knowledge and enlarges the sociological imagination.